Year of the jungle - Collins, Suzanne; Proimos, James (New York : Scholastic Press, 2013)
Suzy spends her year in first grade waiting for her father, who is serving in Vietnam, and when the postcards stop coming she worries that he will never make it home.
Keywords: Children of military personnel -- Juvenile fiction; Vietnam War, 1961-1975 -- Juvenile fiction; Separation (Psychology) -- Juvenile fiction; Fathers and daughters -- Fiction; Soldiers -- Fiction; Vietnam War, 1961-1975 -- Fiction; Separation (Psychology) -- Fiction; Fathers and daughters -- Fiction; Soldiers -- Fiction; Vietnam War, 1961-1975 -- Fiction; Separation (Psychology) -- Fiction